Kajian Manajemen Sanitasi Lingkungan di Pelabuhan Pontianak - Sutrisno, Sutrisno; Raharjo, Mursid; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2009)
ABSTRACT Background: Management of environmental sanitation is an activity to create a condition of healthy & sustainable environment in the Harbor area. Activities at Pontianak Port can cause health problems including pollution of air, soil, water, and food/beverage and may cause of high risk disease. In 2007, total number of disease cases was 1.277. Number of diseases based on environment was 1.057 (82.77%) that consisted of 407 cases of Acute Tract Respiratory Infection (31.87%), 317 cases Diarrhea (24.82%), 105 cases thypus abdominalis (8.22%), 70 cases Allergy Dermatitis (5.48%), 64 cases Conjunctivitis (5.01%), 49 cases Eye Irritation (3.84%), and 45 cases Taenia Pedis (3.52%). Number of diseases which was not based on environment was 220 cases (17.23%) that consisted of 139 cases of General Weakness (10.88%), 59 cases of Hypotension (3.92%), and 31 cases of Gastritis (2.43%). Method: Design of this research was a descriptive-explorative study using qualitative analysis. Number of sample was 22 persons carried out by using a purposive sampling. Data were collected primarily and secondarily to identify and to analyze five aspects of management from six components of harbor’s environmental sanitation. Furthermore, inspection of sanitation, sample test, survey, eradication, and management analysis were performed. Result: Result of this research showed that in drinking water, number of MPN Coli form was high (96, 240, 240, 240, 12). Canteen had a high risk to be polluted for  the procedure (80%), place (100%), and management (100%). Condition of kitchen and cooking tools inside a ship was dirty. There were 10 carts, 5 containers, and 46 toilets. There was no installation of waste water processing and absorption. Vector control used fogging, providing abate powder to eradicate larva of mosquito, and trapping of rat. Inspection of sanitation is sometimes done in a half of sanitation components. Managerial institution had a different focus in terms of a cost and an activity and it is not coordinative. Regulation of Health Ministry No. 340 year1985 had not performed consistently. Community had a complaint in the availability of environmental sanitation facilities quantitatively and qualitatively. Conclusion: Management of environmental sanitation at Pontianak Port has not been in accordance with the health standard which is published by the government (Health Department of Indonesia Republic) and international world (International Health Regulation/ IHR 2005). It is suggested to manage Harbor’s sanitation continually and to implement a strict  regulation in order to reach condition of public health optimally. Keywords : management, environmental sanitation, Harbor, Pontianak